Including personal boundaries scale: development and psychometric properties of a measurement for nurses' self-efficacy toward intimate and sexual behavior in dementia care - Waterschoot, Karien; Roelofs, Tineke S. M.; van Dam, Arno; Luijkx, Katrien G. (Frontiers in Dementia, 2024)
Background Person-centered nursing home care recognizes the intimate and sexual needs of residents with dementia but lacks guidance for nurses to address them while effectively respecting their personal boundaries. The Including Personal Boundaries (IPB) scale was developed to complement clinical and scientific efforts to support both nurse and resident well-being. Methods Through a co-creative process, theoretical principles, day-to-day experiences, and expert knowledge were integrated into an initial nineteen-item version of the IPB scale. The pilot sample comprised 297 Dutch (vocational) nurses in dementia nursing care. Results After Principal Component Analysis, nine items with strong factor loadings (>.6) were retained. Internal reliability measures supported the item selection, such as high internal consistency (α = .866) and adequate corrected item-total correlations (.532 -.781).The presented IPB scale, a nine-item scale, is a short, robust measure to assess nurses' self-efficacy in their capabilities to include personal boundaries (physical and emotional) when confronted with the intimate and sexual behaviors of residents with dementia. Further validation is recommended. The IPB scale could provide valuable insights for research, clinical practice, and education.